2012
DOI: 10.1038/nnano.2012.127
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid passivated colloidal quantum dot solids

Abstract: Colloidal quantum dot (CQD) films allow large-area solution processing and bandgap tuning through the quantum size effect. However, the high ratio of surface area to volume makes CQD films prone to high trap state densities if surfaces are imperfectly passivated, promoting recombination of charge carriers that is detrimental to device performance. Recent advances have replaced the long insulating ligands that enable colloidal stability following synthesis with shorter organic linkers or halide anions, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
1,441
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,141 publications
(1,527 citation statements)
references
References 35 publications
53
1,441
1
12
Order By: Relevance
“…13,15,33,34 It has been reported that MPA passivates the QD surface more completely than EDT. 7,8,21 Our SPS results on PbS-MPA ( Figure 1B), however, reveal the presence of IGS at nearly the same level as those in the PbS-EDT, indicating that the IGS are not due to incomplete ligand passivation. We further performed SPS on ARTICLE ZHANG ET AL.…”
Section: Resultsmentioning
confidence: 68%
“…13,15,33,34 It has been reported that MPA passivates the QD surface more completely than EDT. 7,8,21 Our SPS results on PbS-MPA ( Figure 1B), however, reveal the presence of IGS at nearly the same level as those in the PbS-EDT, indicating that the IGS are not due to incomplete ligand passivation. We further performed SPS on ARTICLE ZHANG ET AL.…”
Section: Resultsmentioning
confidence: 68%
“…34 Since the optoelectronic properties of PbS NC ensembles bear many opportunities for applications in solar cells or photodetectors, a number of ligand exchange procedures with small organic or inorganic molecules as well as single atom passivation strategies have been developed, all of which greatly increase the carrier mobilities within the SL of NCs. 28,33,[35][36][37][38][39][40][41][42][43][44] Due to the short interparticle spacing imposed by these ligands, structural coherence is mostly lost in such superlattices, but in rare cases it has been demonstrated that significant long-range order and even mesocrystallinity can be preserved. 25,35,45 However, a persisting problem of these protocols is that they are prone to introduce defects in the superlattice structure with some degree of granularity and significantly smaller grain sizes, which poses difficulties in determining the angular correlation with a meaningful statistical distribution.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 ), show ultrafast, hot electron transfer to the MO [93]. Considering the similar device architecture in common QD-based PV devices where a MO is used as electron acceptor [80,94,95], this transfer constitutes another potential hot carrier decay channel competing with MEG and hot carrier cooling (see Figure 2). …”
Section: Impacts Of the Qd Surface On Meg In A Device Environmentmentioning
confidence: 96%
“…On a more general level, surface trapped carriers are highly localised and are therefore challenging to extract during solar cell operation [79,80]. Additionally, charge transport properties are intimately linked to the interparticle coupling constant within the QD film [81].…”
Section: Impacts Of the Qd Surface On Meg In A Device Environmentmentioning
confidence: 99%
See 1 more Smart Citation